Dampak Perkuliahan Daring terhadap Prestasi Belajar Mahasiswa Teologi Sekolah Tinggi Teologi Cipanas - Yudha Nata Saputra (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2021)
[THE IMPACT OF ONLINE LECTURES ON THE LEARNING ACHIEVEMENT OF THEOLOGY STUDENTS AT THE CIPANAS THEOLOGICAL COLLEGE] The Covid-19 pandemic has "forced", the education sector is no exception for religious higher education, such as STT to change face-to-face lectures into online lectures. There are many obstacles faced by universities in carrying out online lectures, such as the lack of absorption of lecture material delivered by lecturers, poor internet connections, difficulty adapting to online lectures. Generating worry will have an impact on decreasing student achievement. Several studies on the impact of online lectures on student achievement have been carried out by several universities, but for religious universities, it is still very rare, so it is necessary to immediately conduct research related to the impact of online lectures on student achievement in religious universities. The purpose of this study is to analyze the impact of online lectures on student achievement in theological colleges. The research method used in this research, namely the experimental method, by comparing the average student achievement before online learning and after online learning. The results showed that there was a significant difference in the average student achievement before online learning and after online learning, where student learning achievement after online learning was higher than before online learning.